Fever Management after TEVAR in Patients with Aortic Dissection - Senkulak, Tayfun; Oberhuber, Alexander; Yordanov, Miroslav; Rukosujew, Andreas; Ibrahim, Abdulhakim (Zentralblatt für Chirurgie - Zeitschrift für Allgemeine, Viszeral-, Thorax- und Gefäßchirurgie, 2022)
Background Post-implantation syndrome (PIS) is characterised as a noninfectious continuous fever and a concomitant rise in inflammatory markers shortly after thoracic endovascular aortic repair (TEVAR). This current study aims to analyse the risk factors of PIS, postoperative major adverse cardiac events (MACE), and overall survival as well as the correlation between new-onset mural thrombus and the risk of developing PIS after TEVAR in patients with type B aortic dissection (TBAD). Patients were included who had a B dissection, both acute and chronic forms. In the acute form, both acutely complicated and uncomplicated patients were included in the study. A main point of our investigation is the postoperative fever management of PIS patients.Methods A total of 90 patients with type B dissection underwent TEVAR in the University Hospital of Muenster between 2016 and 2020. The occurrence of PIS was defined as the presence of fever (> 38°C lasting longer than 24 hours in hospital) and leucocytosis (white blood cell count > 12000/µL). Patients with other possible reasons for fever and/or leucocytosis, such as a urinary tract infection (UTI), pneumonia, or sepsis, were excluded beforehand. Besides demographic and operation-related data, inflammatory markers and therapeutic measures were evaluated before and 5 days postoperatively. Computed tomography scans were examined to calculate the volume of preexistent and new-onset mural thrombus after TEVAR.Results Of 90 patients, 40 patients were excluded because of recent infection or bypass surgery. Of the 50 patients included in the study, 10 patients developed post-implantation syndrome. Younger patients significantly more often developed PIS after TEVAR (52.2 ± 11.6 vs. 61.5 ± 13.6, p = 0.045). New-onset thrombus after TEVAR was significantly higher in PIS patients (61 cm³ vs. 12 cm³, p < 0.001) and PIS patients often received more medical examinations (investigation of X-ray, U status, and blood cultures). There was no significant difference in overall survival for 40 months and in the incidence of MACE.Conclusions PIS may be related to an increased rate of new-onset thrombus. A more robust conclusion is not justified according to our study. There is no difference in overall survival.
Keywords: thrombus; thrombus volume; TEVAR; postimplantation syndrome; fever management; PIS